Executive's guide to project management : organizational processes and practices for supporting complex projects - Wysocki, Robert K. (Hoboken, N.J. : John Wiley & Sons, 2011)
'This will be the first book that examines the management of complex and uncertain projects from the perspective of senior management. It is a practical, self-contained'how to' guide for executives and senior managers. It should be their constant companion and desk reference because it collects in one place the relevant'how to' information for understanding and establishing an environment for improving complex project performance. Four major topics are presented: Supporting the organizational challenges to managing complex projects Improving project ROI using agile project portfolio management Improving project success through staffing processes and practices Establishing and maturing an enterprise project support office Each is discussed from the perspective of the organization and how its senior management team can establish structure and processes to support the management of complex projects, programs, and portfolios'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Project management; Executives